Consumption of Dietary Fiber in Relation to Psychological Disorders in Adults - Saghafian, Faezeh; Sharif, Nafiseh; Saneei, Parvane; Keshteli, Ammar Hassanzadeh; Hosseinzadeh-Attar, Mohammad Javad; Afshar, Hamid; Esmaillzadeh, Ahmad; Adibi, Peyman (Frontiers in Psychiatry, 2021)
Background: Previous observational studies suggested a relationship between dietary fiber consumption and mental health, but the findings were conflicting. We evaluated the link between dietary fiber intake and prevalence of depression, anxiety and psychological distress among a large population of Iranian adults. Methods: A cross-sectional study among 3362 Iranian adults working in fifty health centers was done. Data of dietary intakes were collected through a validated semi-quantitative dish-based 106-item food frequency questionnaire (FFQ). Anxiety, depression and psychological distress were defined based on Iranian validated version of Hospital Anxiety and Depression Scale (HADS) and General Health Questionnaire (GHQ). Results: After adjustment for potential confounders, participants in the top quartile of total dietary fiber intake had a 33 and 29% lower risk of anxiety and high psychological distress [OR: 0.67; 95% CI: 0.48, 0.95) and (OR: 0.71; 95% CI: 0.53, 0.94), respectively], compared to the bottom quartile of intake. The highest total dietary fiber intake was also inversely related to lower risk of depression in women (OR: 0.63; 95% CI: 0.45, 0.88), but not in men. Among overweight or obese participants, higher intake of dietary fiber was related to decreased risk of high psychological distress (OR: 0.52; 95% CI: 0.34, 0.79). High level of dietary fiber intake was related to lower risk of anxiety in normal-weight individuals (OR: 0.50; 95% CI: 0.31, 0.80). Conclusion: Significant inverse associations between total dietary fiber intake with anxiety and high psychological distress were found in Iranian adults. More consumption of dietary fiber was also related to reduced odds of depression in women. More investigations with prospective nature are needed to affirm these findings.